Ancient Fennoscandian genomes reveal origin and spread of Siberian ancestry in Europe. Issue 1 (December 2018) - Lamnidis, Thiseas; Majander, Kerttu; Jeong, Choongwon; Salmela, Elina; Wessman, Anna; Moiseyev, Vyacheslav; Khartanovich, Valery; Balanovsky, Oleg; Ongyerth, Matthias; Weihmann, Antje; Sajantila, Antti; Kelso, Janet; et al.
Abstract European population history has been shaped by migrations of people, and their subsequent admixture. Recently, ancient DNA has brought new insights into European migration events linked to the advent of agriculture, and possibly to the spread of Indo-European languages. However, little is known about the ancient population history of north-eastern Europe, in particular about populations speaking Uralic languages, such as Finns and Saami. Here we analyse ancient genomic data from 11 individuals from Finland and north-western Russia. We show that the genetic makeup of northern Europe was shaped by migrations from Siberia that began at least 3500 years ago. This Siberian ancestry was subsequently admixed into many modern populations in the region, particularly into populations speaking Uralic languages today. Additionally, we show that ancestors of modern Saami inhabited a larger territory during the Iron Age, which adds to the historical and linguistic information about the population history of Finland. Populations from North-eastern Europe, in particular those speaking Uralic languages, carry additional ancestry in similarity with modern East Asian populations. Here, the authors analyse ancient genomic data from 11 individuals from Finland and Northwest Russia, and identify genomic signals of migrations from Siberia that began at least 3500 years ago.